Evolution of the MLO gene families in octoploid strawberry (Fragaria ×ananassa) and progenitor diploid species identified potential genes for strawberry powdery mildew resistance. (1st July 2021) - Tapia, Ronald R; Barbey, Christopher R; Chandra, Saket; Folta, Kevin M; Whitaker, Vance M; Lee, Seonghee
Abstract: Powdery mildew (PM) caused by Podosphaera aphanis is a major fungal disease of cultivated strawberry. Mildew Resistance Locus O ( MLO ) is a gene family described for having conserved seven-transmembrane domains. Induced loss-of-function in specific MLO genes can confer durable and broad resistance against PM pathogens. However, the genomic structure and potential role of MLO genes for PM resistance have not been characterized yet in the octoploid cultivated strawberry. In the present study, MLO gene families were characterized in four diploid progenitor species ( Fragaria vesca, F . iinumae, F . viridis, and F . nipponica ) and octoploid cultivated ( Fragaria ×ananassa) strawberry, and potential sources of MLO -mediated susceptibility were identified. Twenty MLO sequences were identified in F. vesca and 68 identified in F. ×ananassa . Phylogenetic analysis divided diploid and octoploid strawberry MLO genes into eight different clades, in which three FveMLO ( MLO10, MLO17, and MLO20 ) and their twelve orthologs of FaMLO were grouped together with functionally characterized MLO genes conferring PM susceptibility. Copy number variations revealed differences in MLO composition among homoeologous chromosomes, supporting the distinct origin of each subgenome during the evolution of octoploid strawberry. Dissecting genomic sequence and structural variations in candidate FaMLO genes revealed their potential role associated with genetic controls and functionality in strawberry against PM pathogen. Furthermore, the gene expression profiling and RNAi silencing of putative FaMLO genes in response to the pathogen indicate the function in PM resistance. These results are a critical first step in understanding the function of strawberry MLO genes and will facilitate further genetic studies of PM resistance in cultivated strawberry.